Investigating the impact of an efficacy-based nursing program integrated with nutritional intervention strategies on the outcomes of multiple myeloma patients with renal failure - Liu, Tingting; Lv, Jing; Xu, Luxiang; Zhang, Xiaomei; Xiao, Qing; Li, Jun; Zhang, Zhaoli; Liu, Yao (Frontiers in Nutrition, 2025)
ObjectiveTo explore the effect of nursing scheme based on efficacy theory combined with nutritional intervention on patients with multiple myeloma (MM) complicated with renal failure.MethodsNinety-two patients with MM complicated with renal failure in our hospital from April 2022 to April 2024 were randomly divided into control group (46 cases, using conventional nursing) and observation group (46 cases, using nursing scheme based on efficacy theory combined with nutritional intervention). The CDSES score of self-efficacy, CD-RISC score of resilience, CFS score of cancer-related fatigue, nutrition related indicators (ALB, Hb, PA) and FLIC score of quality of life were compared between the two groups.ResultsAfter the intervention, both groups showed increased CDSES and CD-RISC scores, with the observation group significantly higher than controls. And the levels of ALB, Hb and PA in the observation group were significantly higher than those in the control group. Cancer fatigue scale (CFS) scores at T1, T2, and T3 were reduced from baseline (T0) in both groups; and the observation group was significantly lower than the control group. After the intervention, the scores of the four dimensions of good body and ability, good psychology, difficulties caused by cancer and good society of the two groups were significantly improved, and the scores of the observation group were higher than those of the control group; The scores of nausea dimension in the two groups were significantly lower than those before the intervention, and the control group decreased more than the observation group (p < 0.05).ConclusionThe efficacy theory-based nursing plan combined with nutritional intervention benefits MM patients with renal failure. It improves self-efficacy and psychological resilience, reduces cancer-related fatigue, and enhances nutritional status and overall quality of life.